Antimicrobial and Physical Characteristics of Cassava Starch Biodegradable Film Enhanced with Citronella Extract - Wibowo Condro; Wijayanti Nur; Haryanti Pepita; Syerin Nabila Fitria; Fitrianti Annisa; Tien Dat Huynh (E3S Web of Conferences)
Plastic packaging has been reported to pose environmental concerns due to its non-biodegradability. Biodegradable films, derived from renewable resources, offer a promising alternative due to their biodegradability properties. In addition, antimicrobial active packaging, using natural ingredients can enhance food safety and extend shelf life. Citronella is well documented regarding its antimicrobial activity potentially serves as natural ingredient in the production of biodegradable films. This study aimed to investigate the effects of extract types and concentrations of citronella on physical, and antimicrobial properties of biodegradable films. Results indicate that citronella extract significantly enhanced the antimicrobial activity, biodegradability, and certain physical properties of biodegradable films. Moreover, extract types and concentrations influenced transparency, color parameters, and water vapor transmission rate. Higher extract concentrations led to increased antimicrobial inhibition but decreased transparency. These findings suggest that citronella extract-added cassava starch biodegradable film could offer a promising alternative to traditional plastic packaging toward improving environmental sustainability and food safety. Further research is required to optimize the formulation and scale-up production for practical application.